Impact of the ileal microbiota on colon cancer - Roberti, Maria Paula; Rauber, Conrad; Kroemer, Guido; Zitvogel, Laurence (Seminars in cancer biology, 2022)
Besides tumor cell-intrinsic oncogenic pathways, host and environmental factors have a major impact on cancer immunosurveillance and the efficacy of immunotherapeutics. Several modalities of anticancer treatments including immunogenic chemotherapies and immune checkpoint inhibitors lose their efficacy in patients treated with broad-spectrum antibiotics, pointing to a key role for the gut microbiota. The complex interactions between intestinal microbes, gut immunity and anti-tumor responses constitute an emerging field of investigation. In this work, we revise key primary literature, with an emphasis on recent mechanistic insights, unraveling the interplay between the immunosurveillance of colon cancers and ileal factors including the local microbiota, tissue architecture and immune system.
Online verfügbar 5. Oktober 2021, Artikelversion 19. Oktober 2022
Gesehen am 07.06.2023